Preparation method of elastic comfortable composite fabric
By forming semicircular breathable holes on denim fabrics, and using hydrophilic aerogel and sea urchin-like Fe3O4 to enhance elasticity, combined with pressure fit and flocking technology, the problem of denim fabrics lack of elasticity is solved, achieving high elasticity, breathability and comfort of the fabrics.
Patent Information
- Application Number
- CN202411892529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The lack of elasticity of existing denim fabrics leads to poor wear comfort and cannot meet people's demand for improved functional fabrics.
A method of preparing elastic and comfortable composite fabrics is adopted, from top to bottom, a flocking layer, a denim fabric layer, an elastic filling layer, and a denim fabric layer. By forming semicircular breathable holes on the surface of the fibers and using hydrophilic acrylic aerogel as the elastic filling layer, sea urchin-like Fe3O4 is added to enhance the elasticity and hydrophilicity of the aerogel, and by vulcanizing cross-linking, it forms a film package to impart it to the surface of the aerogel frame, combining pressure bonding and flocking technology to form a mosaic structure.
It improves the elasticity and moisture absorption of the fabric, forms breathable channels and windproof effects, and significantly improves the comfort and functionality of the fabric.
Smart Images

Figure BDA0005200976320000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multi-layer fabrics, in particular to a method for preparing an elastic and comfortable composite fabric. Background Art
[0002] As people's living standards continue to improve, people's functional requirements for fabrics are gradually increasing. For example, when people choose clothes in the hot summer, they tend to choose comfortable, high-quality, moisture-wicking, and refreshing fabrics. Currently, denim fabrics on the market lack elasticity and are less comfortable to wear as outerwear fabrics. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an elastic and comfortable composite fabric to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an elastic and refreshing composite fabric, wherein the elastic and refreshing composite fabric comprises a flocking layer, a denim fabric layer, an elastic filling layer, and a denim fabric layer from top to bottom;
[0005] The elastic and refreshing composite fabric is prepared by the following method:
[0006] (1) An aqueous solution of ferric chloride and an aqueous solution of ferrous sulfate were mixed in a volume ratio of 1:1, two permanent magnets were set at the left and right ends of the container, the pH of the solution was adjusted to 11.5, and the solution was kept warm at 90-95°C for 12 h in a nitrogen atmosphere with a magnetic field strength of 0.2-0.35 T. The solid was filtered out, washed with deionized water for several times until the pH of the washing solution was 7, and dried to obtain sea urchin-like Fe3O4;
[0007] (2) acrylic acid, sea urchin-shaped Fe3O4 and water are mixed, permanent magnets are set at the upper and lower ends of the container, ultrasonic dispersion is performed at 400-600W for 10 minutes, and the mixture is allowed to stand for 30 minutes at a magnetic field strength of 0.3-0.5T. Ammonium persulfate (0.002-0.01 times the weight of acrylic acid) and diallylmalonic acid (0.1-0.5 times the weight of acrylic acid) are added, and ultrasonic dispersion is continued for 10 minutes. The mixture is reacted at a magnetic field strength of 0.3-0.5T and 55-65°C for 6-8 hours, and then taken out, ethanol aqueous solution is added to swell for 30-44 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel;
[0008] (3) Putting the acrylic rubber into a double-roll rubber mixer and plasticizing for 5 to 10 minutes, placing it 2 cm below an ultraviolet-ozone light source and irradiating it for 5 to 15 minutes to obtain a hydrophilic rubber; then mixing the hydrophilic rubber, diisopropylbenzene peroxide, magnesium oxide, and ethyl isocyanate acrylate for 10 minutes, cutting it into pieces, adding a 60 wt % toluene ethanol solution, and stirring at 400 rpm for 30 minutes to obtain a rubber liquid;
[0009] (4) The composite aerogel and rubber liquid were mixed in a ratio of 1 g:10 mL, vacuumed, kept for 6 to 8 hours, taken out, dried at 60° C. for 12 hours, and then vulcanized at a pressure of 10 MPa and 170° C. for 30 minutes to obtain an elastic aerogel;
[0010] (5) The denim fabric is placed in an oxygen atmosphere and treated with low-temperature plasma for 30 to 60 seconds, the elastic aerogel is evenly spread on the treated denim fabric, and then covered with another layer of treated denim fabric, and pressure is applied to fit and flock to obtain an elastic and comfortable composite fabric.
[0011] Furthermore, the concentration of the ferric chloride aqueous solution in step (1) is 0.2 mol / L.
[0012] Furthermore, the concentration of the ferrous sulfate aqueous solution in step (1) is 0.4 mol / L.
[0013] Furthermore, in step (1), the drying temperature is 60° C. and the drying time is 12 h.
[0014] Furthermore, in step (2), the weight ratio of acrylic acid, sea urchin-like Fe3O4 and water is 1:0.2-0.5:2-10.
[0015] Furthermore, the concentration of the ethanol aqueous solution in step (2) is 80 wt %.
[0016] Furthermore, in step (3), the mass ratio of the hydrophilic rubber, dicumyl peroxide, magnesium oxide and ethyl isocyanate acrylate is 70-100:2-5:2-5:4-6.
[0017] Furthermore, the concentration of the rubber liquid in step (3) is 0.02 to 0.05 g / mL.
[0018] Furthermore, the weight of the denim fabric in step (5) is 180 g / m 2 .
[0019] Furthermore, the pressure in step (5) is 2 to 5 MPa.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The present invention performs plasma controllable etching on the fabric to form concave semicircular air holes on the fiber surface, and then uses hydrophilic acrylic aerogel as the elastic filling layer between the double-layer fabrics. During the preparation of the aerogel, sea urchin-shaped Fe3O4 is added, and a relative magnetic field is set up in the vertical direction, so that the Fe3O4 is concentrated on the upper and lower surfaces of the aerogel, thereby forming an aerogel with needle-like protrusions on the surface, and then a hydrophilic rubber dispersion is soaked in the aerogel, and the two are vulcanized and cross-linked, so that the hydrophilic rubber forms a film to be coated on the surface of the aerogel skeleton, thereby greatly improving the elasticity and hydrophilicity of the aerogel, thereby The elasticity and moisture absorption of the fabric are improved. At the same time, the holes of the aerogel form perspiration channels and ventilation holes to improve the comfort of the fabric. The semicircular ventilation holes on the fabric part are connected with the aerogel, which further extends the ventilation channel and improves the comfort of the fabric. Then the fabric is pressed together. The needle-like whiskers on the surface of the aerogel penetrate the upper and lower layers, so that the filling layer and the fabric are inlaid, thereby fixing the filling layer between the fabrics, thereby giving the fabric elasticity and breathability. Then, flocking is done on one side of the fabric to form fiber fluff. When the wind blows outside, the fiber fluff blocks the ventilation hole and acts as a check valve to achieve a windproof effect. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] Example 1; (1) 0.2 mol / L ferric chloride aqueous solution and 0.4 mol / L ferrous sulfate aqueous solution were mixed in a volume ratio of 1:1, two permanent magnets were set at the left and right ends of the container, the pH of the solution was adjusted to 11.5, and the magnetic field strength was 0.2T and kept at 90°C for 12 h under a nitrogen atmosphere. The solid was filtered and washed with deionized water for several times until the pH of the washing solution was 7, and dried at 60°C for 12 h to obtain sea urchin-shaped Fe3O4;
[0024] (2) Acrylic acid, sea urchin-shaped Fe3O4, and water were mixed in a weight ratio of 1:0.2:2, permanent magnets were set up at the upper and lower ends of the container, ultrasonic dispersion was performed at 400W for 10 minutes, and the mixture was allowed to stand for 30 minutes at a magnetic field strength of 0.3T. Ammonium persulfate (0.002 times the weight of acrylic acid) and diallylmalonic acid (0.1 times the weight of acrylic acid) were added, and ultrasonic dispersion was continued for 10 minutes. The mixture was reacted at a magnetic field strength of 0.3T and 55°C for 6 hours, and then taken out, 80wt% ethanol aqueous solution was added to swell for 30 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel;
[0025] (3) Put the acrylic rubber into a two-roll rubber mixer and plasticize for 5 minutes, then place it 2 cm below an ultraviolet-ozone light source for irradiation for 5 minutes to obtain a hydrophilic rubber; then mix the hydrophilic rubber, diisopropylbenzene peroxide, magnesium oxide, and ethyl isocyanate acrylate in a mass ratio of 70:2:2:4 for 10 minutes, cut it into pieces, add 60 wt% toluene ethanol solution, and stir at 400 rpm for 30 minutes to obtain a rubber liquid with a concentration of 0.02 g / mL;
[0026] (4) The composite aerogel and rubber liquid were mixed in a ratio of 1 g:10 mL, vacuumed, kept for 6 h, taken out, dried at 60 ° C for 12 h, and then vulcanized at a pressure of 10 MPa and 170 ° C for 30 min to obtain elastic aerogel;
[0027] (5) Set the weight to 180g / m 2 The denim fabric was placed in an oxygen atmosphere and treated with low-temperature plasma for 30 seconds. The elastic aerogel was evenly laid on the treated denim fabric, and then covered with another layer of treated denim fabric. The fabric was laminated and flocked under a pressure of 2MPa to obtain an elastic and comfortable composite fabric.
[0028] Example 2; (1) 0.2 mol / L ferric chloride aqueous solution and 0.4 mol / L ferrous sulfate aqueous solution were mixed in a volume ratio of 1:1, two permanent magnets were set at the left and right ends of the container, the pH of the solution was adjusted to 11.5, and the magnetic field strength was 0.3T and kept at 92°C for 12 h under a nitrogen atmosphere. The solid was filtered and washed with deionized water for several times until the pH of the washing solution was 7, and dried at 60°C for 12 h to obtain sea urchin-shaped Fe3O4;
[0029] (2) Acrylic acid, sea urchin-shaped Fe3O4, and water were mixed in a weight ratio of 1:0.235:6, permanent magnets were set up at the upper and lower ends of the container, ultrasonic dispersion was performed at 500W for 10 minutes, and the mixture was allowed to stand for 30 minutes at a magnetic field strength of 0.4T. Ammonium persulfate (0.006 times the weight of acrylic acid) and diallylmalonic acid (0.3 times the weight of acrylic acid) were added, and ultrasonic dispersion was continued for 10 minutes. The reaction was carried out at a magnetic field strength of 0.4T and 60°C for 7 hours, and the mixture was taken out, and 80wt% ethanol aqueous solution was added to swell for 38 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel;
[0030] (3) Put the acrylic rubber into a two-roll rubber mixer and plasticize for 7 minutes, then place it 2 cm below an ultraviolet-ozone light source and irradiate it for 10 minutes to obtain a hydrophilic rubber; then mix the hydrophilic rubber, diisopropylbenzene peroxide, magnesium oxide, and ethyl isocyanate acrylate in a mass ratio of 88:3.5:3:5 for 10 minutes, cut it into pieces, add 60 wt % toluene ethanol solution, and stir at 400 rpm for 30 minutes to obtain a rubber liquid with a concentration of 0.04 g / mL;
[0031] (4) The composite aerogel and rubber liquid were mixed in a ratio of 1 g:10 mL, vacuumed, kept for 7 h, taken out, dried at 60 ° C for 12 h, and then vulcanized at a pressure of 10 MPa and 170 ° C for 30 min to obtain elastic aerogel;
[0032] (5) Set the weight to 180g / m 2 The denim fabric was placed in an oxygen atmosphere and treated with low-temperature plasma for 45 seconds. The elastic aerogel was evenly laid on the treated denim fabric, and then covered with another layer of treated denim fabric. The fabric was laminated and flocked under a pressure of 3 MPa to obtain an elastic and comfortable composite fabric.
[0033] Example 3; (1) 0.2 mol / L ferric chloride aqueous solution and 0.4 mol / L ferrous sulfate aqueous solution were mixed in a volume ratio of 1:1, two permanent magnets were set at the left and right ends of the container, the pH of the solution was adjusted to 11.5, and the magnetic field strength was 0.35T and kept at 95°C for 12h under a nitrogen atmosphere. The solid was filtered and washed with deionized water for several times until the pH of the washing solution was 7, and dried at 60°C for 12h to obtain sea urchin-shaped Fe3O4;
[0034] (2) Acrylic acid, sea urchin-shaped Fe3O4, and water were mixed in a weight ratio of 1:0.5:10, permanent magnets were set up at the upper and lower ends of the container, ultrasonic dispersion was performed at 600W for 10 minutes, and the mixture was allowed to stand for 30 minutes at a magnetic field strength of 0.5T. Ammonium persulfate (0.01 times the weight of acrylic acid) and diallylmalonic acid (0.5 times the weight of acrylic acid) were added, and ultrasonic dispersion was continued for 10 minutes. The mixture was reacted at a magnetic field strength of 0.5T and 65°C for 8 hours, and then taken out, 80wt% ethanol aqueous solution was added to swell for 44 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel;
[0035] (3) Put the acrylic rubber into a two-roll rubber mixer and plasticize it for 10 minutes, then place it 2 cm below an ultraviolet-ozone light source and irradiate it for 15 minutes to obtain a hydrophilic rubber; then mix the hydrophilic rubber, diisopropylbenzene peroxide, magnesium oxide, and ethyl isocyanate acrylate in a mass ratio of 100:5:5:6 for 10 minutes, cut it into pieces, add 60 wt% toluene ethanol solution, and stir at 400 rpm for 30 minutes to obtain a rubber liquid with a concentration of 0.05 g / mL;
[0036] (4) The composite aerogel and rubber liquid were mixed in a ratio of 1 g:10 mL, vacuumed, kept for 8 h, taken out, dried at 60 ° C for 12 h, and then vulcanized at a pressure of 10 MPa and 170 ° C for 30 min to obtain elastic aerogel;
[0037] (5) Set the weight to 180g / m 2The denim fabric was placed in an oxygen atmosphere and treated with low-temperature plasma for 60 seconds. The elastic aerogel was evenly laid on the treated denim fabric, and then covered with another layer of treated denim fabric. The fabric was laminated and flocked under a pressure of 5 MPa to obtain an elastic and comfortable composite fabric.
[0038] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: acrylic acid, microsphere Fe3O4, and water are mixed in a weight ratio of 1:0.235:6, permanent magnets are set at the upper and lower ends of the container, 500W ultrasonic dispersion is performed for 10 minutes, and the magnetic field intensity is 0.4T. Let it stand for 30 minutes, add ammonium persulfate 0.006 times the weight of acrylic acid and diallylmalonic acid 0.3 times the weight of acrylic acid, continue ultrasonic dispersion for 10 minutes, and react at a magnetic field intensity of 0.4T and 60°C for 7 hours. Take it out, add 80wt% ethanol aqueous solution to swell for 38 hours, and freeze-dry at -40°C for 1 hour to obtain a composite aerogel; the remaining steps are the same as those in Example 2.
[0039] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: acrylic acid, sea urchin-shaped Fe3O4 and water are mixed in a weight ratio of 1:0.235:6, ultrasonically dispersed at 500W for 10 minutes, ammonium persulfate 0.006 times the weight of acrylic acid and diallylmalonic acid 0.3 times the weight of acrylic acid are added, ultrasonic dispersion is continued for 10 minutes, reacted at 60°C for 7 hours, taken out, 80wt% ethanol aqueous solution is added to swell for 38 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel; the remaining steps are the same as those in Example 2.
[0040] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: the acrylate rubber is placed in a two-roll rubber mixer and plasticized for 7 minutes, then mixed with diisopropyl peroxide, magnesium oxide, and ethyl isocyanate acrylate in a mass ratio of 88:3.5:3:5 for 10 minutes, cut into pieces, added with 60wt% toluene ethanol solution, and stirred at 400rpm for 30 minutes to obtain a rubber liquid with a concentration of 0.04g / mL; the remaining steps are the same as in Example 2.
[0041] Comparative Example 4; The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: the composite aerogel and rubber liquid are mixed in a ratio of 1g:10mL, vacuumed, kept for 7h, taken out, and dried at 60°C for 12h to obtain the elastic aerogel; the remaining steps are the same as Example 2.
[0042] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (3) and step (4), and step (5) is changed to: the gram weight is 180g / m 2The denim fabric is placed in an oxygen atmosphere and treated with low-temperature plasma for 45 seconds. The composite aerogel is evenly laid on the treated denim fabric, and then covered with another layer of treated denim fabric. The fabric is laminated under a pressure of 3 MPa and flocked to obtain a stretchy and comfortable composite fabric. The remaining steps are the same as those in Example 2.
[0043] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (5) is different. Step (5) is changed to: evenly laying the elastic aerogel on the denim fabric, then covering it with another layer of treated denim fabric, laminating it under a pressure of 3 MPa, and flocking it to obtain an elastic and comfortable composite fabric; the remaining steps are the same as Example 2.
[0044] Comparative Example 7; The difference between Comparative Example 7 and Example 2 is that step (5) is different, and step (5) is changed to: the gram weight is 180g / m 2 The denim fabric is placed in an oxygen atmosphere and treated with low-temperature plasma for 45 seconds. The elastic aerogel is evenly laid on the treated denim fabric, and then covered with another layer of treated denim fabric, and laminated under a pressure of 3 MPa to obtain an elastic and comfortable composite fabric. The remaining steps are the same as in Example 2.
[0045] Effect example
[0046] Table 1 below shows the performance analysis results of the elastic and refreshing composite fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0047] Table 1
[0048]
[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A stretchy and comfortable composite fabric, characterized in that: The elastic and comfortable composite fabric comprises a flocking layer, a denim fabric layer, an elastic filling layer, and a denim fabric layer from top to bottom; The elastic and refreshing composite fabric is prepared by the following method: (1) An aqueous solution of ferric chloride and an aqueous solution of ferrous sulfate were mixed in a volume ratio of 1:1, two permanent magnets were set at the left and right ends of the container, the pH of the solution was adjusted to 11.5, and the solution was kept warm at 90-95°C for 12 h in a nitrogen atmosphere with a magnetic field strength of 0.2-0.35 T. The solid was filtered out, washed with deionized water for several times until the pH of the washing solution was 7, and dried to obtain sea urchin-like Fe3O4; (2) acrylic acid, sea urchin-shaped Fe3O4 and water are mixed, permanent magnets are set at the upper and lower ends of the container, ultrasonic dispersion is performed at 400-600W for 10 minutes, and the mixture is allowed to stand for 30 minutes at a magnetic field strength of 0.3-0.5T. Ammonium persulfate (0.002-0.01 times the weight of acrylic acid) and diallylmalonic acid (0.1-0.5 times the weight of acrylic acid) are added, and ultrasonic dispersion is continued for 10 minutes. The mixture is reacted at a magnetic field strength of 0.3-0.5T and 55-65°C for 6-8 hours, and then taken out, ethanol aqueous solution is added to swell for 30-44 hours, and freeze-dried at -40°C for 1 hour to obtain a composite aerogel; (3) Putting the acrylic rubber into a double-roll rubber mixer and plasticizing for 5 to 10 minutes, placing it 2 cm below an ultraviolet-ozone light source and irradiating it for 5 to 15 minutes to obtain a hydrophilic rubber; then mixing the hydrophilic rubber, diisopropylbenzene peroxide, magnesium oxide, and ethyl isocyanate acrylate for 10 minutes, cutting it into pieces, adding a 60 wt % toluene ethanol solution, and stirring at 400 rpm for 30 minutes to obtain a rubber liquid; (4) The composite aerogel and rubber liquid were mixed in a ratio of 1 g:10 mL, vacuumed, kept for 6 to 8 hours, taken out, dried at 60° C. for 12 hours, and then vulcanized at a pressure of 10 MPa and 170° C. for 30 minutes to obtain an elastic aerogel; (5) The denim fabric is placed in an oxygen atmosphere and treated with low-temperature plasma for 30 to 60 seconds, the elastic aerogel is evenly spread on the treated denim fabric, and then covered with another layer of treated denim fabric, and pressure is applied to fit and flock to obtain an elastic and comfortable composite fabric.
2. The elastic and refreshing composite fabric according to claim 1, characterized in that: The concentration of the ferric chloride aqueous solution in step (1) is 0.2 mol / L.
3. The elastic and refreshing composite fabric according to claim 1, characterized in that: The concentration of the ferrous sulfate aqueous solution in step (1) is 0.4 mol / L.
4. The elastic and refreshing composite fabric according to claim 1, characterized in that: The drying temperature in step (1) is 60° C. and the drying time is 12 h.
5. The elastic and refreshing composite fabric according to claim 1, characterized in that: The weight ratio of the acrylic acid, sea urchin-shaped Fe3O4 and water in step (2) is 1:0.2-0.5:2-10.
6. The elastic and refreshing composite fabric according to claim 1, characterized in that: The concentration of the ethanol aqueous solution in step (2) is 80wt%.
7. The elastic and refreshing composite fabric according to claim 1, characterized in that: The mass ratio of the hydrophilic rubber, dicumyl peroxide, magnesium oxide and ethyl isocyanate acrylate in step (3) is 70-100:2-5:2-5:4-6.
8. The elastic and refreshing composite fabric according to claim 1, characterized in that: The concentration of the rubber liquid in step (3) is 0.02-0.05 g / mL.
9. The elastic and refreshing composite fabric according to claim 1, characterized in that: The weight of the denim fabric in step (5) is 180 g / m 2 .
10. The elastic and refreshing composite fabric according to claim 1, characterized in that: The pressure in step (5) is 2 to 5 MPa.
Citation Information
Patent Citations
Fe3O4@bacterial cellulose / graphene oxide composite aerogel as well as preparation method and application thereof
CN109499546A
Fiber-based aerogel adsorbent and application thereof in adsorbing dyeing wastewater
CN110170315A
Flame-retardant heat-conducting agent for general rubber as well as preparation method and application of flame-retardant heat-conducting agent
CN115124765A
Cited By
Waterproof thermal insulation material and application thereof
CN120327067A